The Relationship between Breastfeeding Time and Stress Levels in Post Partum Mothers at Sukodono Helath Center, Lumajang Regency - Isnaeni Arista Dewi; Nur Hamin; Iit Ernawati (Fakultas Teknologi dan Manajemen Kesehatan, 2023)
Exclusive breastfeeding is breastfeeding alone without other food and drink until the baby is 6 months old, then breastfeeding must continue until the baby is 2 years old even though the baby has been introduced to food. A decrease in the breastfeeding process can be caused by stress in postpartum mothers. The purpose of this study was to analyze the relationship between breastfeeding time and stress levels in post partum mothers at the Sukodono Health Center. Research design cross-sectional was used for 55 breastfeeding mothers in the working area of the Sukodono Public Health Center. Questionnaire of respondent characteristics and Parenting Stress Index Short Form is used to observe the interval of breastfeeding and the stress level of postpartum mothers. Spearman Rank is used to answer the purpose of this study. Based on the results of the study, there was a relationship between breastfeeding time and stress levels in postpartum mothers (p-value = 0.05). The results showed that 41 respondents (74.5%) with good breastfeeding time and respondents with low stress levels are 40 people (72.7%). A good breastfeeding time can increase baby's growth and development to be optimal. Stress levels may be affected by the relationship between mother and baby.